Magnetic Mineral Diagenesis in a Newly Discovered Active Cold Seep Site in the Bay of Bengal - Badesab, F.; Dewangan, P.; Gaikwad, V. (Frontiers in Earth Science, 2020)
Diagenetically formed magnetic minerals at marine methane seep sites are potential archive of past fluid flow and could provide important constraints on the evolution of past methane seepage dynamics and gas hydrate formation over geologic time. In this study, we carried out integrated rock magnetic, and mineralogical analyses, supported by electron microscope observations, on a seep impacted sediment core to unravel the linkage between greigite magnetism, methane seepage dynamics, and evolution of shallow gas hydrate system in the K-G basin. Three sediment magnetic zones (MZ-1, MZ-2, and MZ-3) have been identified based on the down-core variations in rock magnetic properties. Two events of intense methane seepage are identified. Repeated occurences of authigenic carbonates throughout the core indicate the episodic intensification of anaerobic oxidation of methane (AOM) at the studied site. Marked depletion in magnetic susceptibility manifested by the presence of chemosynthetic shells (Calyptogena Sp), methane-derived authigenic carbonates, and abundant pyrite grains provide evidences on intense methane seepage events at this site. Fracture-controlled fluid transport supported the formation of gas hydrates (distributed and massive) at this site. Three greigite bearing sediment intervals (G1, G2, G3) within the magnetically depleted zone (MZ-2) are probably the paleo-gas hydrate (distributed-type vein filling) intervals. A strong linkage among clay content, formation of veined hydrate deposits, precipitation of authigenic carbonates and greigite preservation is evident. Hydrate crystallizes within faults/fractures formed as the methane gas migrates through the gas hydrate stability zone (GHSZ). Formation of authigenic carbonate layers coupled with clay deposits restricted the upward migrating methane, which led to the formation of distributed-type vein filling hydrate deposits. A closed system created by veined hydrates trapped the sulfide and limited its availability thereby, causing arrestation of pyritization and favoured the formation and preservation of greigite in G1, G2, G3.